Impact of 6-month earlier versus postponed initiation of rotigotine on long-term outcome: post hoc analysis of patients with early Parkinson's disease with mild symptom severity. (July 2015) - Timmermann, Lars; Asgharnejad, Mahnaz; Boroojerdi, Babak; Dohin, Elisabeth; Woltering, Franz; Elmer, Lawrence W
<x xml:space="preserve">Abstract</x> Objective: Investigate impact of 6-month earlier versus postponed initiation of rotigotine in patients with early Parkinson's disease (PD) with mild symptom severity. Background: Long-term benefit of rotigotine in early-PD has been demonstrated: SP702 (NCT00594165) and SP716 (NCT00599196) were long-term, open-label extensions of double-blind, placebo-controlled studies of 6-month maintenance; rotigotine was well tolerated for up to 6 years, and demonstrated efficacy (Unified Parkinson's Disease Rating Scale [UPDRS] II + III below baseline) for ∼ 2 years (SP702) and ∼ 4 years (SP716). Methods: Post hoc analysis of patients at Hoehn and Yahr 1–2; groups defined by treatment received in 6-month double-blind studies: 'Rotigotine–Rotigotine' received rotigotine (n = 221), 'Placebo–Rotigotine' received placebo (n = 125). Results: At the start of open-label rotigotine maintenance, UPDRS II + III mean ± SD change from double-blind baseline was: −8.5 ± 10.6 'Rotigotine–Rotigotine', −7.7 ± 9.0 'Placebo–Rotigotine.' After this initial improvement scores gradually increased: It took ∼ 45 months for mean scores to cross baseline in 'Rotigotine–Rotigotine', and ∼ 21 months in 'Placebo–Rotigotine.' At the time mean UPDRS II + III had crossed baseline in 'Placebo–Rotigotine' (open-label week 84; ∼ 21 months), treatment difference (LS-mean) to 'Rotigotine–Rotigotine' change from baseline was −3.89 (95% CI −6.94, −0.84); p = 0.013. Conclusions: In this post hoc analysis, 6-month earlier initiation of rotigotine resulted in slower return to baseline mean UPDRS II + III; initiation of rotigotine in patients with minimal/no functional disability or impairment may lead to an extended benefit.